2023
DOI: 10.1021/acs.biochem.2c00541
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Burden Borne by Fumarase: Enzymatic Hydration of an Olefin

Abstract: Fumarate hydratase (FH) is a remarkable catalyst that decreases the free energy of the catalyzed reaction by 30 kcal mol −1 , much larger than most exceptional enzymes with extraordinary catalytic rates. Two classes of FH are observed in nature: class-I and class-II, which have different folds, yet catalyze the same reversible hydration/dehydration reaction of the dicarboxylic acids fumarate/malate, with equal efficiencies. Using class-I FH from the hyperthermophilic archaeon Methanocaldococcus jannaschii (Mj)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 85 publications
(142 reference statements)
2
11
0
Order By: Relevance
“…Apart from activity on (S)-malate (Bellur et al, 2023), as shown in Figure S2A, MjFH was found to be active on (S,S)-tartrate corroborating previous reports on other Class-I FHs . The enzyme was inactive on (R,R)-tartrate, and (R)-malate.…”
Section: Substrate Specificity Of Mjfh and Ecl-ttdsupporting
confidence: 90%
See 4 more Smart Citations
“…Apart from activity on (S)-malate (Bellur et al, 2023), as shown in Figure S2A, MjFH was found to be active on (S,S)-tartrate corroborating previous reports on other Class-I FHs . The enzyme was inactive on (R,R)-tartrate, and (R)-malate.…”
Section: Substrate Specificity Of Mjfh and Ecl-ttdsupporting
confidence: 90%
“…This apart G216 of the KGXGS motif contacts C2  OH (Figure 4a). All these residues superpose well on the structure of Mj FH (Bellur et al, 2023). Examination of the active site in the modeled structure of Ec L‐TTD did not reveal any difference in the orientation of the ligand‐binding and catalytic residues, that could account for the altered substrate stereospecificity preference in L‐TTD compared with Class‐I FHs (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations